Effect of photoperiod on the cultural morphology of Rhizoctonia solani isolates of maize from Yogyakarta and Central Java, Indonesia - SRI WAHYUNI BUDIARTI; RUDY LUKMAN; CHRISTANTI SUMARDIYONO; ARIF WIBOWO; ACHMADI PRIYATMOJO (Society for Indonesian Biodiversity, 2019)
Abstract. Budiarti SW, Lukman R, Sumardiyono C, Wibowo A, Priyatmojo A. 2019. Effect of photoperiod on the cultural morphology of Rhizoctonia solani isolates of maize from Yogyakarta and Central Java, Indonesia. Biodiversitas 20: 2028-2038. Banded leaf and sheath blight (BLSB) caused by Rhizoctonia solani Kuhn is a significant constraint of maize production in Indonesia, especially within the last several years. R. solani is an important soil-borne necrotrophic fungal pathogen which is known to be sensitive to different environmental conditions. The differential response of fungi to light and dark is important to study, especially of those causing disease to crop plant as it helps to reveal the factors regulating the pathogenicity of the fungus. This study aims to determine the effect of light duration on the mycelial development and sclerotia formation of R. solani isolates obtained from different locations in Yogyakarta Special Region and Central Java, Indonesia. Ten isolates of R. solani collected from different geographic regions in Yogyakarta Special Region, and Central Java from maize (nine isolates) and rice (one isolate) were exposed to three different light conditions: 12 h alternating light/dark, continuous darkness, and continuous light. Cultural morphology and sclerotial characteristics were recorded for each isolate. All isolates revealed great diversity in terms of cultural and morphological characteristics after exposure to three different light conditions. Under complete darkness, the mycelial growth phase was extended, and a fluffy mass of mycelia was produced. All isolates showed abundant growth under the 12 h alternating light/dark condition than under the continuous dark and continuous light conditions. Sclerotia were initiated earlier under the 12 h alternating light/dark condition than under other conditions. The 12 h alternating light/dark condition also induced number and heavier weight of sclerotia compared with those produced under the continuous light and continuous dark conditions. The modifications in light condition exert a significant impact on some R. solani isolates.